TAYANGAN UPIN DAN IPIN PADA PERILAKU POSITIF DI SEKOLAH DASAR NEGERI KARTIKA SEJAHTERA 01 (Jurnal Ilmu Komunikasi, 2020)
This study aims to determine the effect of Upin and Ipin films on the episodes of the Night of Fasting on positive behavior This research uses quantitative methods, while the number of respondents in this study amounted to 90 people using purposive sampling techniques. Data collection is done by observing and distributing questionnaires and collecting data from reading sources that are relevant to the research problem. The results of the study carried out known R square value of 0.485 which means that the contribution of the influence of the effect of impressions on the behavior of 48.5%, while the remaining 52.5% is influenced by other factors not included in this study. Furthermore, the hypotheses of the calculated t value of 9.060> t table 1.662, it can be concluded that (Ho) is rejected and (Ha) is accepted, which means that there is a significant influence between Upin and Ipin impressions on positive behavior of the sample children, SDN Kartika Sejahtera 01.